Anti-dense fine speckled 70 (DFS70) autoantibodies: correlates and increasing prevalence in the United States - Dinse, Gregg E.; Zheng, Bing; Co, Caroll A.; Parks, Christine G.; Weinberg, Clarice R.; Miller, Frederick W.; Chan, Edward K. L. (Frontiers in Immunology, 2023)
Objective. Recent studies report high-titer anti-dense fine speckled 70 (DFS70) autoantibodies in persons with inflammatory conditions, but the clinical significance remains unclear. Our goals were to estimate anti-DFS70 autoantibody prevalence, identify correlates, and assess time trends. Methods. Serum antinuclear antibodies (ANA) were measured by indirect immunofluorescence assay on HEp-2 cells in 13,519 participants ≥12 years old from three time periods (1988-1991, 1999-2004, 2011-2012) of the National Health and Nutrition Examination Survey. ANA-positive participants with dense fine speckled staining were evaluated for anti-DFS70 antibodies by enzyme-linked immunosorbent assay. We used logistic models adjusted for survey-design variables to estimate period-specific anti-DFS70 antibody prevalence in the US, and we further adjusted for sex, age, and race/ethnicity to identify correlates and assess time trends. Results. Women were more likely than men (odds ratio (OR)=2.97), black persons were less likely than white persons (OR=0.60), and active smokers were less likely than nonsmokers (OR=0.28) to have anti-DFS70 antibodies. The prevalence of anti-DFS70 antibodies increased from 1.6% in 1988-1991 to 2.5% in 1999-2004 to 4.0% in 2011-2012, which corresponds to 3.2 million, 5.8 million, and 10.4 million seropositive individuals, respectively. This increasing time trend in the US population (P<0.0001) was modified in some subgroups and was not explained by concurrent changes in tobacco smoke exposure. Some, but not all, anti-DFS70 antibody correlates and time trends resembled those reported for total ANA. Conclusion. More research is needed to elucidate anti-DFS70 antibody triggers, their pathologic or potentially protective influences on disease, and their possible clinical implications.